E-Wom Positif dan Sikap Wisatawan dalam Meningkatkan Niat Berkunjung pada Generasi Millenial (Studi pada Geowisata Selo Bonang Kabupaten Jember) - Sri Lilik Puji Rahayu (Jurnal Ilmu Manajemen, 2020)
Before conducting tourism activities, prospective tourists will consider several factors including e-WOM, and their attitude towards tourist destinations before carrying out activities that will give rise to the intention of visiting tourist destinations. This study aims to determine the effect of positive eWOM and intention to travel to Selo Bonang Geotourism by using mediating variables from tourist attitudes. This research uses quantitative data. The sampling technique used is non-probability sampling with the type of judgmental sampling. In this study, the sample used was 220 respondents using non-probability sampling techniques. Data is processed using path analysis techniques. The results of this study indicate that positive e-WOM has a positive and significant influence on tourist attitudes, tourist attitudes have a positive and significant effect on visit intention, and positive e-WOM has a positive and significant impact on visit intention, with mediation proven partially.